Pendampingan Orang Tua Terhadap Aktivitas Belajar Anak di Masa Pandemi Covid-19 - Kristian Adi Santoso (Sekolah Tinggi Alkitab Jember, 2022)
Parental assistance to children in learning activities at home during the Covid-19 pandemic is mandatory. The form of assistance provided by parents, namely: preparing learning equipment; monitoring children while at home; controlling children's learning time well, and helping children overcome obstacles in learning. In theory, parental assistance has an influence on children's learning activities. Children’s learning activities can be reflected in activities: paying close attention to the teacher's explanation; understanding the teacher's explanation; studying student material; noting down the teacher's explanation; responding to teacher questions; playing an active role in group discussions and the courage to express opinions. The research method uses a correlational. The research was conducted at SMP Negeri 1 Waingapu. The results of the study provide information that there is a positive and significant influence, the variable of parental assistance on children's learning activities can be seen from the correlation coefficient of 0.547 which is significant at  = 0.05. This means that the assistance provided by parents is getting better, so children's learning activities will also increase. AbstrakPendampingan orang tua kepada anak-anak dalam kegiatan belajar di rumah pada masa pandemik Covid-19 wajib dilakukan. Bentuk pendampingan yang diberikan orang tua, yaitu : menyiapkanperlengkapan belajar; memantau anak selama berada di rumah; mengontrol waktu belajar anak dengan baik dan membantu anak dalam mengatasi kendala dalam belajar. Secara teori pendampingan orang tua memberikan pengaruh terhadap aktitivas belajar anak. Aktivitas belajar anak dapat tercermin dari aktivias : memperhatikan dengan sungguh penjelasan guru; memahami penjelasan guru; mempelajari materi pelajaram; mencatat penjelasan guru; memberi respons atas pertanyaan guru; berperan aktif dalam diskusi kelompok dan keberanian menyampaikan pen-dapat. Penelitian ini menggunakan metode kuantitatif dengan pendekatan korelasional. Penelitian dilakukan di SMP Negeri 1 Waingapu. Hasil penelitian memberikan infromasi yaitu terdapat penga-ruh yang positif dan signifikan,variabel pendampingan orang tua pada aktivitas belajar anak, dapat dilihat dari nilaikorelasi sebesar 0,547 dan p-value 0,000 pada =0,05. Berarti semakin tinggi intensitas pendampingan orang tua, maka semakin tinggi pula, aktivitas belajar anak.